Trends and outcomes of pulmonary valve replacement in tetralogy of Fallot. (15th January 2020) - Egbe, Alexander C.; Vallabhajosyula, Saraschandra; Connolly, Heidi M.
Abstract: Background: Pulmonary valve replacement (PVR) is associated with improvement in symptoms and right ventricular remodeling in patients with tetralogy of Fallot (TOF). There are limited population-based data about outcomes after PVR. We therefore hypothesized a temporal increase in annual volume of PVR and decrease in in-hospital mortality after PVR in the United States. Methods: We reviewed the National Inpatient Sample (NIS) for PVR performed in adults (>18 years) with TOF, 2000–2014. The primary outcome was trends in admissions for PVR, in-hospital mortality after PVR, and age at time of PVR. In order to assess trends, we divided the study period into tertiles: early era (2000–2004), mid era (2005–2009) and late era (2010–2014). Results: There were 18, 353 admissions in adults with TOF diagnosis, of which PVR was performed in 1230 (6.7%), and 90 (7.3%) were transcatheter PVRs. The median age at PVR was 34 years and in-hospital mortality was 1.5%. Comparisons by study era showed temporal increase in the proportion of admissions for PVR (3.7% vs 6.3% vs 9.6%, p  < 0.001), decrease in in-hospital mortality (4.1% vs 1.2% vs 0.8%, p  = 0.002), and a decrease in age at the time of PVR (35.8 vs 33.8 vs 31.0 years, p  < 0.001). Conclusions: The proportion of admissions for PVR increased while in-hospital mortality and age at time of PVR decreased over time. A younger age at the time of PVR highlights important concerns and knowledge gaps about the cumulative lifetime risk of reinterventions and prosthetic valve endocarditis. Further studies are required to address these knowledge gaps. Highlights: Proportion of admissions for valve replacement (PVR) increased over time. In-hospital mortality and age at time of PVR decreased over time. Results highlight potential risk of cumulative lifetime risk of reinterventions.